Swedenborg, politicien et prophète - Roy-Di Piazza, V (L'Harmattan, 2023)
This article provides the first detailed study of the parliamentary career, political influence, and political thought of the Swedish philosopher and theologian Emanuel Swedenborg (1688-1772).